Syntactic mechanisms in the transition from academic written to oral discourses - Nausa, Ricardo (Colombian Applied Linguistics Journal, 2017)
This article presents the results of a pilot study that sought to identify: (1) the syntactic mechanisms that a group of PhD-level Colombian EAP students used to express originally written content in oral presentations, and (2) how those mechanisms can be used to describe the differences of performance between high- and low-rated presentations. To achieve these objectives, a discourse analysis comparison of eight parallel pairs of texts (eight essays and their corresponding oral presentation transcriptions) was performed. Quantitative analyses were also performed to confirm the qualitative analyses. Syntactic modifications to clause structure and heavily modified noun phrases were identified as some of the mechanisms that students used to transition from written to oral discourse. The analysis of these mechanisms includes the description of further sub-mechanisms, the linguistic resources that are implemented, their pragmatic appropriateness, and their grammatical correctness. Among the sub-mechanisms deemed as useful indicators of quality of oral performance are topicalization and reduction of heavily modified NPs. Other sub-mechanisms such as the rhematization of NP modifiers were not useful to discriminate among levels of oral performance. This report ends with the presentation of the implications and limitations of the study, and the perspectives for future research.